Covering medical device and method of manufacturing the same

By forming a specific copolymer layer on the surface of the medical device, the problem of difficulty in achieving sufficient hydrophilicity, slipibility and lipid adhesion inhibition in the prior art is solved, and a higher biocompatibility and sense of use are achieved.

CN119654171APending Publication Date: 2025-03-18TORAY INDUSTRIES INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380057372.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-02-28
Filing Date
2023-08-09
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art is difficult to achieve sufficient hydrophilicity, slipibility and lipid adhesion inhibition on medical devices.

Method used

By forming a hydrophilic polymer layer on the surface of the medical device, the layer contains a specific compound a1 and a compound a2 having an amide group, and the copolymerization ratio is 1/99 to 90/10, and it is colonized on the surface of the device by heating process.

Benefits of technology

It realizes the full hydrophilicity, slipibility and lipid adhesion inhibition of the surface of medical equipment, and improves the compatibility and sense of use of the biological body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005259898920000021
    Figure BDA0005259898920000021
  • Figure BDA0005259898920000022
    Figure BDA0005259898920000022
  • Figure BDA0005259898920000061
    Figure BDA0005259898920000061
Patent Text Reader

Abstract

The purpose of the present invention is to provide: a covering medical device that imparts lipid adhesion suppression properties in addition to imparting sufficient hydrophilicity and slippery properties; and a simple method for producing the covering medical device. Provided are: a covering medical device provided with a medical device and a hydrophilic polymer layer that covers the surface of the medical device, the hydrophilic polymer layer containing a hydrophilic polymer A, the hydrophilic polymer (A) contains, as monomer units, a compound (a1) having a specific structure and a compound (a2) having an amide group, and the copolymerization ratio of the compound (a1) to the compound (a2) is 1 / 99-90 / 10 by mass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to covered medical devices and methods of making the same. Background Art

[0002] Conventionally, medical devices using soft materials such as silicone rubber and hydrogel or medical devices using hard materials such as metal and glass have been used for various purposes in various fields.

[0003] When a medical device is inserted into a living body or attached to a living body surface, surface modification of the medical device for the purpose of improving its biocompatibility becomes important. If, in addition to improving biocompatibility, the medical device is given properties such as hydrophilicity, slipperiness, and lipid adhesion inhibition through surface modification, it can be expected to improve the user's feeling of use, reduce discomfort, and improve symptoms.

[0004] As a method for modifying the surface of a medical device, for example, the following method is known: the surface of the medical device is modified by immersing the medical device in a solution of pH 6 to 9 containing one or more polymers formed from a compound having an amide group such as N,N-dimethylacrylamide or vinyl pyrrolidone at room temperature, or by heating the solution after immersion (Patent Documents 1 to 3).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: International Publication No. 2017 / 018425

[0008] Patent Document 2: International Publication No. 2015 / 119256

[0009] Patent Document 3: Japanese Patent No. 5154231 Summary of the invention

[0010] Problems to be solved by the invention

[0011] However, the inventions disclosed in Patent Documents 1 to 3 are not inventions capable of imparting sufficient hydrophilicity, lubricity, etc. to the surface of a medical device, and further, are not methods capable of imparting lipid adhesion inhibition properties to a medical device.

[0012] Therefore, an object of the present invention is to provide a covered medical device which is imparted with sufficient hydrophilicity and lubricity and also imparts lipid adhesion inhibition properties, and a simple method for producing the same.

[0013] Solutions for solving problems

[0014] In order to achieve the above-mentioned purpose, the present invention is a medical device covering, which comprises a medical device and a hydrophilic polymer layer covering the surface of the medical device, wherein the hydrophilic polymer layer comprises a hydrophilic polymer A, and the hydrophilic polymer A comprises a compound a1 represented by the following general formula (I) or the following general formula (II) and a compound a2 having an amide group as monomer units, and the copolymerization ratio of the above-mentioned compound a1 to the above-mentioned compound a2 is 1 / 99 to 90 / 10 in terms of mass ratio.

[0015] [Chemistry 1]

[0016]

[0017] In the general formula (I), R 1 represents a hydrogen atom or a methyl group, and X represents an oxygen atom or NR 2 , R 2 represents a hydrogen atom or an alkyl group, and m represents an integer of 1 to 30.

[0018] [Chemistry 2]

[0019]

[0020] In the general formula (II), R 1 represents a hydrogen atom or a methyl group, and X represents an oxygen atom or NR 2 , R 2 represents a hydrogen atom or an alkyl group, n represents 2 or 4, k represents 3 or 4, a represents an integer of 0 to 30, b represents an integer of 1 to 30, and Y represents a hydrogen atom, methyl, ethyl, propyl, isopropyl or butyl.

[0021] In addition, the present invention covers a method for producing a medical device, comprising: (A) a contact step of placing the medical device in a container and bringing the medical device into contact with a solution a containing a hydrophilic polymer A; and (C) a heating step of heating the container, wherein the hydrophilic polymer A comprises a compound a1 represented by the general formula (I) or the general formula (II) and a compound a2 having an amide group as monomer units, and the copolymerization ratio of the compound a1 to the compound a2 is 1 / 99 to 90 / 10 in terms of mass ratio,

[0022] In the general formula (I), R 1 represents a hydrogen atom or a methyl group, and X represents an oxygen atom or NR 2 , R 2 represents a hydrogen atom or an alkyl group, and m represents an integer of 1 to 30;

[0023] In the general formula (II), R 1 represents a hydrogen atom or a methyl group, and X represents an oxygen atom or NR 2 , R 2represents a hydrogen atom or an alkyl group, n represents 2 or 4, k represents 3 or 4, a represents an integer of 0 to 30, b represents an integer of 1 to 30, and Y represents a hydrogen atom, methyl, ethyl, propyl, isopropyl or butyl;

[0024] The pH of the solution a after the heating step is 6.1 to 8.0.

[0025] Effects of the Invention

[0026] According to the present invention, a covered medical device can be provided which has sufficient hydrophilicity and lubricity required for medical devices and has lipid adhesion inhibition properties. In addition, according to the manufacturing method of the present invention, the covered medical device can be obtained by a simple process. DETAILED DESCRIPTION

[0027] The covered medical device of the present invention comprises a medical device and a hydrophilic polymer layer covering the surface of the medical device.

[0028] Examples of medical devices included in the covered medical device of the present invention include ophthalmic lenses, skin covering materials, wound covering materials, skin protective materials, skin drug carriers, infusion tubes, gas delivery tubes, drainage tubes, blood circuits, covering tubes, catheters, stents, sheaths, biosensor chips, artificial heart-lungs, or endoscope covering materials. Examples of ophthalmic lenses include contact lenses, intraocular lenses, artificial corneas, corneal inserts, corneal onlays, or spectacle lenses.

[0029] As materials constituting medical devices, both water-containing materials and low-water-containing materials can be used. As water-containing materials, for example, hydrogels or silicone hydrogels can be cited. When the medical device is a contact lens, hydrogels are preferred because they can form a surface layer that has high lipid adhesion inhibition, excellent hydrophilicity and slipperiness, and durability, and can easily maintain the effect during long-term wear. As low-water-containing materials, for example, low-water-containing soft materials or low-water-containing hard materials can be cited. It should be noted that low-water-containing materials refer to materials with a water content of 10% by mass or less.

[0030] In the following, the United States Adopted Names (USAN) are sometimes used to indicate the name of a hydrogel or silicone hydrogel. In USAN, symbols such as A, B, and C are sometimes added at the end to indicate the material variant. In this specification, all variants are indicated when no suffix symbol is added. For example, when abbreviated as "ocufilcon", it indicates all variants of ocufilcon such as "ocufilconA", "ocufilconB", "ocufilconC", "ocufilconD", "ocufilconE" or "ocufilconF".

[0031] Examples of the hydrogel include tefilcon, tetrafilcon, hefilcon, mafilcon, polymacon, hioxifilcon, alfafilcon, omafilcon, hixoifilcon, nelfilcon, nesofilcon, hilafilcon, acofilcon, deltafilcon, etafilcon, focofilcon, ocufilcon, phemfilcon, methafilcon, or vilfilcon.

[0032] When the medical device is a contact lens containing a hydrogel, it belongs to Group 1 to Group 4 of the classification of contact lenses regulated by the US Food and Drug Administration (FDA), preferably Group 2 or Group 4 showing good hydrophilicity, and more preferably Group 4.

[0033] Examples of the nonionic hydrogels belonging to the first group and having a water content of less than 50% by mass include tefilcon, tetrafilcon, helfilcon, mafilcon, polymacon, and hioxifilcon.

[0034] Examples of the nonionic hydrogels belonging to the second group and having a water content of 50% by mass or more include alfafilcon, omafilcon, hixoifilcon, nelfilcon, nesofilcon, hilafilcon and acofilcon. Preferred are omafilcon, hixoifilcon, nelfilcon and nesofilcon which show good hydrophilicity, more preferably omafilcon or hixoifilcon, and still more preferably omafilcon.

[0035] Examples of ionic hydrogels belonging to the third group and having a water content of less than 50% by mass include deltafilcon.

[0036] Examples of the ionic hydrogel having a water content of 50% by mass or more and belonging to the fourth group include etafilcon, focofilcon, ocufilcon, phemfilcon, methafilcon and vilfilcon. Preferred examples are etafilcon, focofilcon, ocufilcon and phemfilcon, which show good hydrophilicity. More preferred examples are etafilcon and ocufilcon, and even more preferred are etafilcon.

[0037] When the medical device is a contact lens containing silicone hydrogel, it preferably belongs to Group 5, which is the classification of contact lenses regulated by the US Food and Drug Administration (FDA).

[0038] The silicone hydrogel belonging to the fifth group is preferably a hydrophilic polymer having silicon atoms in the main chain and / or side chain, and examples thereof include copolymers of a siloxane bond-containing monomer and a hydrophilic monomer. Examples of such copolymers include lotrafilcon, galyfilcon, narafilcon, senofilcon, comfilcon, enfilcon, balafilcon, efrofilcon, fanfilcon, somofilcon, samfilcon, olifilcon, asmofilcon, formofilcon, stenfilcon, abafilcon, mangofilcon, riofilcon, sifilcon, larafilcon and delefilcon. Preferred are lotrafilcon, galyfilcon, narafilcon, senofilcon, comfilcon, enfilcon, stenfilcon, somofilcon, delefilcon, balafilcon and samfilcon, more preferred are lotrafilcon, narafilcon, senofilcon, comfilcon and enfilcon, and even more preferred are narafilcon, senofilcon and comfilcon.

[0039] As the low-water-content soft material or the low-water-content hard material, when the medical device is a contact lens, a silicon atom-containing material showing high oxygen permeability capable of sufficiently supplying oxygen to the cornea is preferred.

[0040] As the low-water-content hard material, a low-water-content hard material belonging to the contact lens classification stipulated by the US Food and Drug Administration (FDA) is preferred.

[0041] As the low water content hard material, a polymer having a silicon atom such as a siloxane bond in the main chain and / or the side chain is preferred, and more preferably tris(trimethylsiloxy)silylpropyl methacrylate having high oxygen permeability, polydimethylsiloxane having double bonds at both ends, or a homopolymer obtained using silicone-containing acrylate or silicone-containing methacrylate, or a copolymer thereof with other monomers, etc.

[0042] Specifically, the low water-containing hard material is preferably selected from neofocon, pasifocon, telefocon, silafocon, paflufocon, petrafocon and fluorofocon. Among them, neofocon, pasifocon, telefocon or silafocon is more preferred, neofocon, pasifocon or telefocon is further preferred, and neofocon is particularly preferred from the perspective of showing good lipid adhesion inhibition and antifouling properties.

[0043] When the medical device is a device other than a contact lens, the low-water-containing hard material is preferably polyethylene, polypropylene, polysulfone, polyetherimide, polystyrene, polymethyl methacrylate, polyamide, polyester, epoxy resin, polyurethane or polyvinyl chloride. Among them, polysulfone, polystyrene, polymethyl methacrylate, polyurethane or polyamide is more preferred, and polymethyl methacrylate is further preferred from the perspective of exhibiting good lipid adhesion inhibition and antifouling properties.

[0044] Examples of the low-water-content soft material include elastofilcon, which is disclosed in International Publication No. 2013 / 024799 and has a water content of 10% by mass or less, an elastic modulus of 100 to 2,000 kPa, and a tensile elongation of 50 to 3,000%.

[0045] In the present invention, the medical device can impart appropriate lipid adhesion inhibition to the surface of the medical device regardless of whether the medical device has a water content or a low water content. In order to impart appropriate lipid adhesion inhibition, the water content of the medical device is preferably 0.0001% by mass or more, more preferably 0.001% by mass or more. In addition, the water content of the medical device is preferably 80% by mass or less, more preferably 70% by mass or less, and even more preferably 60% by mass or less.

[0046] When the medical device is a contact lens, the water content of the medical device is preferably 15% by mass or more, more preferably 20% by mass or more, from the viewpoint of easily ensuring the movement of the lens in the eye.

[0047] The hydrophilic polymer A is hydrophilic. Here, "hydrophilic" means that the polymer can dissolve 0.0001 parts by mass or more in 100 parts by mass of water or a mixed solution of 100 parts by mass of water and 100 parts by mass of tert-butyl alcohol at room temperature (20 to 23° C.). Preferably, the polymer can dissolve 0.01 parts by mass or more, more preferably, 0.1 parts by mass or more, and even more preferably, 1 part by mass or more.

[0048] The hydrophilic polymer layer of the medical device covered by the present invention is characterized in that it contains a hydrophilic polymer A, which contains a compound a1 represented by the following general formula (I) or the following general formula (II) and a compound a2 having an amide group as monomer units, and the copolymerization ratio of the above-mentioned compound a1 and the above-mentioned compound a2 is 1 / 99 to 90 / 10 in terms of mass ratio.

[0049] As the compound a1 and the compound a2, a single monomer may be used, or a plurality of monomers having different structures may be used.

[0050] [Chemistry 3]

[0051]

[0052] In the general formula (I), R 1 represents a hydrogen atom or a methyl group, and X represents an oxygen atom or NR 2 , R 2 represents a hydrogen atom or an alkyl group, and m represents an integer of 1 to 30.

[0053] R 2 When it is an alkyl group, it may be linear or branched, but is preferably an alkyl group having 1 to 10 carbon atoms. 2 , for example, methyl, ethyl, propyl, 2-propyl, butyl, 2-butyl, tert-butyl, pentyl, 2-pentyl, 3-pentyl, hexyl, heptyl or octyl can be mentioned.

[0054] From the viewpoint of appropriate hydrophilicity and ease of polymerization, m is preferably 2 to 30. The lower limit of m is more preferably 3, further preferably 4, and particularly preferably 5. The upper limit of m is more preferably 25, further preferably 20, and particularly preferably 10.

[0055] [Chemistry 4]

[0056]

[0057] In the general formula (II), R 1 represents a hydrogen atom or a methyl group, and X represents an oxygen atom or NR 2 , R 2 represents a hydrogen atom or an alkyl group, n represents 2 or 4, k represents 3 or 4, a represents an integer of 0 to 30, b represents an integer of 1 to 30, and Y represents a hydrogen atom, methyl, ethyl, propyl, isopropyl or butyl.

[0058] R 2 When it is an alkyl group, it may be linear or branched, but is preferably an alkyl group having 1 to 10 carbon atoms. 2 , for example, methyl, ethyl, propyl, 2-propyl, butyl, 2-butyl, tert-butyl, pentyl, 2-pentyl, 3-pentyl, hexyl, heptyl or octyl can be mentioned.

[0059] From the viewpoint of appropriate hydrophilicity and ease of polymerization, a is preferably 0 to 25. The lower limit of a is more preferably 0, further preferably 2, and particularly preferably 3. The upper limit of a is more preferably 20, further preferably 15, and particularly preferably 10.

[0060] From the viewpoint of appropriate hydrophilicity and ease of polymerization, b is preferably 1 to 25. The lower limit of b is more preferably 1, further preferably 2, and particularly preferably 3. The upper limit of b is more preferably 20, further preferably 15, and particularly preferably 10.

[0061] From the viewpoint of easiness of forming the covering layer, Y is more preferably hydrogen, methyl, ethyl, propyl or isopropyl, and most preferably hydrogen or methyl.

[0062] As the compound a1, from the viewpoint of ease of polymerization, solubility in a water-soluble solvent, and ease of imparting hydrophilicity, a compound represented by the general formula (I) is more preferred.

[0063] As the compound a2 having an amide group, from the viewpoint of ease of polymerization, a compound having an acrylamide group or a methacrylamide group, or N-vinylcarboxylic acid amide (including a cyclic compound) is preferred.

[0064] Specific examples thereof include N-vinylpyrrolidone, N-vinylcaprolactam, N-vinylacetamide, N-methyl-N-vinylacetamide, N-vinylformamide, N,N-dimethylacrylamide, N-isopropylacrylamide, N-methylacrylamide, N-ethylacrylamide, N-butylacrylamide, N-tert-butylacrylamide, N-hydroxymethylacrylamide, N-methoxymethylacrylamide, N-ethoxymethylacrylamide, N-propoxymethylacrylamide, N-isopropoxymethylacrylamide, N-(2-hydroxyethyl)acrylamide, N-butoxymethylacrylamide, N-isobutoxymethylacrylamide, N-hydroxymethylmethylacrylamide, N-methoxymethylmethylacrylamide, N-ethoxymethylmethylacrylamide, N-propoxymethylmethylacrylamide, N-butoxymethylmethylacrylamide, N-isobutoxymethylmethylacrylamide, N-hydroxymethylmethylacrylamide, N-methoxymethylmethylacrylamide, N-ethoxymethylmethylacrylamide, N-propoxymethylmethylacrylamide, N-butoxymethylmethylacrylamide, N-isobutoxymethylmethylacrylamide, acryloylmorpholine or acrylamide. In order to improve lubricity, N-vinyl pyrrolidone, N-isopropylacrylamide or N,N-dimethylacrylamide is preferred, N-isopropylacrylamide or N,N-dimethylacrylamide is more preferred, and N,N-dimethylacrylamide is further preferred.

[0065] For the hydrophilic polymer A, as a monomer unit, it can also be contained in the form of one or more copolymers of other compounds other than the compound a1 shown in the general formula (I) or the general formula (II) and the compound a2 having an amide group. As such other compounds, for example, glyceryl acrylate, glyceryl methacrylate, N-(4-hydroxyphenyl) maleimide, hydroxystyrene, vinyl alcohol (vinyl carboxylate as a precursor), (meth) hydroxyethyl acrylate, (meth) hydroxypropyl acrylate or (meth) hydroxybutyl acrylate can be cited. In order to improve the antifouling property for body fluids, glyceryl acrylate, glyceryl methacrylate or vinyl alcohol are preferred, and glyceryl acrylate or glyceryl methacrylate is more preferred. In addition, as other compounds, compounds showing functions such as hydrophilicity, antibacterial property, antifouling property, and pharmacological efficacy can also be used.

[0066] When the hydrophilic polymer A contains the compound a1 having the specific structure as a monomer unit, the hydrophilic polymer A is easily dissolved in water and exhibits a hydrophilic function, thereby forming a surface having not only hydrophilicity but also lipid adhesion inhibition.

[0067] When the hydrophilic polymer A contains the compound a2 having an amide group as a monomer unit, the hydrophilic polymer A exhibits appropriate viscosity when dissolved in water, and a surface having not only hydrophilicity but also lubricity can be formed.

[0068] In order to easily show lipid adhesion inhibition, durable hydrophilicity and other functions, the copolymerization ratio of the above-mentioned compound a1 and the above-mentioned compound a2 is in the range of 1 / 99 to 90 / 10 in terms of mass ratio. That is, in all the monomer units contained in the hydrophilic polymer A, the total of compound a1 and compound a2 is set to 100% by mass, and the proportion of compound a1 needs to be 1% by mass or more, preferably 10% by mass or more, and more preferably 30% by mass or more. In addition, from the perspective of ease of polymerization, the proportion of compound a1 needs to be 99% by mass or less, preferably 90% by mass or less, more preferably 85% by mass or less, and further preferably 80% by mass or less. In addition, the total hydrophilic polymer A is set to 100% by mass, and the proportion of compound a2 needs to be 10% by mass or more, preferably 12% by mass or more, more preferably 15% by mass or more, and further preferably 20% by mass or more. The proportion of the compound a2 needs to be 90% by mass or less, preferably 90% by mass or less, more preferably 80% by mass or less, and further preferably 70% by mass or less.

[0069] When other compounds other than the above-mentioned compound a1 and the above-mentioned compound a2 are copolymerized as the third monomer component, the copolymerization ratio of the third monomer component is more preferably 2% by mass or more, further preferably 5% by mass or more, and particularly preferably 10% by mass or more. In addition, the copolymerization ratio of the third monomer component is more preferably 90% by mass or less, further preferably 80% by mass or less, and particularly preferably 70% by mass or less.

[0070] When the copolymerization ratio of the compound a1 represented by the general formula (I), the compound a2 having an amide group and the third monomer component is within the above range, functions such as lubricity and antifouling properties against body fluids are easily exhibited.

[0071] In order to increase the adsorption force of the hydrophilic polymer A on the surface of the medical device and give the medical device sufficient lipid adhesion inhibition, the weight average molecular weight of the hydrophilic polymer A is preferably 2000 to 1500000. The weight average molecular weight is more preferably 5000 or more, further preferably 10000 or more, and particularly preferably 100000 or more. In addition, the weight average molecular weight is more preferably 1200000 or less, further preferably 1000000 or less, and particularly preferably 900000 or less. The weight average molecular weight referred to here is a weight average molecular weight converted to polyethylene glycol measured by gel permeation chromatography using an aqueous solvent as a developing solvent.

[0072] In addition, the method for producing a covered medical device of the present invention is characterized by comprising: (A) a contact step of placing the medical device in a container and bringing the medical device into contact with a solution a containing a hydrophilic polymer A; and (C) a heating step of heating the container, wherein the hydrophilic polymer A comprises a compound a1 represented by the following general formula (I) or the following general formula (II) and a compound a2 having an amide group as monomer units, and the copolymerization ratio of the compound a1 to the compound a2 is 1 / 99 to 90 / 10 in terms of mass ratio,

[0073] [Chemistry 5]

[0074]

[0075] In the general formula (I), R 1 represents a hydrogen atom or a methyl group, and X represents an oxygen atom or NR 2 , R 2 represents a hydrogen atom or an alkyl group, and m represents an integer of 1 to 30;

[0076] [Chemistry 6]

[0077]

[0078] In the general formula (II), R 1 represents a hydrogen atom or a methyl group, and X represents an oxygen atom or NR 2 , R 2 represents a hydrogen atom or an alkyl group, n represents 2 or 4, k represents 3 or 4, a represents an integer of 0 to 30, b represents an integer of 1 to 30, and Y represents a hydrogen atom, methyl, ethyl, propyl, isopropyl or butyl;

[0079] The pH of the solution a after the heating step is 6.1 to 8.0.

[0080] The concentration of the hydrophilic polymer A in the solution a containing the hydrophilic polymer A is preferably in the range of 0.0001 to 30% by mass in order to make the viscosity of the solution a moderate. The concentration of the hydrophilic polymer A is more preferably 0.001% by mass or more, and further preferably 0.005% by mass or more. In addition, the concentration of the hydrophilic polymer A is more preferably 10.0% by mass or less, further preferably 5.0% by mass or less, further preferably 1.0% by mass or less, and particularly preferably 0.5% by mass or less.

[0081] As the solvent of the solution a containing the hydrophilic polymer A, from the aspect of ease of operation, preferably a water-soluble organic solvent or water, or a mixed solvent thereof, more preferably a mixed solvent of water and a water-soluble organic solvent or water, further preferably water. As the water-soluble organic solvent, preferably a water-soluble alcohol, more preferably a water-soluble alcohol having a carbon number of 6 or less, further preferably a water-soluble alcohol having a carbon number of 5 or less. The solution a may further contain a buffer and other additives.

[0082] Examples of the buffer contained in solution a include boric acid, borates (e.g., sodium borate), citric acid, citrates (e.g., potassium citrate), bicarbonates (e.g., sodium bicarbonate), phosphate buffer (e.g., Na2HPO4, NaH2PO4, or KH2PO4), TRIS (tris(hydroxymethyl)aminomethane), 2-bis(2-hydroxyethyl)amino-2-(hydroxymethyl)-1,3-propanediol, bisaminopolyol, triethanolamine, ACES (N-(2-acetamido)-2-aminoethanesulfonic acid), BES (N,N-bis(2-hydroxyethyl)-2-aminoethanesulfonic acid), HEPES (4-(2-hydroxyethyl)-1-piperazine ethanesulfonic acid), MES (2-(N-morpholino)ethanesulfonic acid), MOPS (3-[N-morpholino]-propanesulfonic acid), PIPES (piperazine-N,N'-bis(2-ethanesulfonic acid) or TES (N-[tris(hydroxymethyl)methyl]-2-aminoethanesulfonic acid) or salts thereof. In order to achieve the desired pH, the proportion of the buffer in solution a can be appropriately adjusted, and the proportion is generally preferably 0.001 to 2.000% by mass. The proportion of the buffer is more preferably 0.010% by mass or more, and further preferably 0.050% by mass or more. In addition, the proportion of the buffer is more preferably 1.000% by mass or less, and further preferably 0.300% by mass or less.

[0083] The solution a provided in the contacting step is preferably prepared by dissolving the hydrophilic polymer A in a buffer solution containing a solvent and a buffer. The pH of the buffer solution used to prepare the solution a is preferably in a physiologically acceptable range, i.e., 6.3 to 7.8. The pH of the buffer solution is more preferably 6.5 or more, and further preferably 6.8 or more. In addition, the pH of the buffer solution is more preferably 7.6 or less, and further preferably 7.4 or less.

[0084] As a container for storing the medical device in the contact process, for example, when the medical device is an ophthalmic lens, a vial or a blister container for packaging ophthalmic lenses can be cited. The blister container generally includes a plastic base portion surrounded by a raised flat flange around the edge of its air cell, and a soft cover sheet bonded to the flat flange to seal the air cell.

[0085] As materials for the plastic base portion, there can be listed, for example, fluororesins, polyamides, polyacrylates, polyethylene, nylons, olefin copolymers (for example, copolymers of polypropylene and polyethylene), polyethylene terephthalate, polyvinyl chloride, amorphous polyolefins, polycarbonates, polysulfones, polybutylene terephthalate, polypropylene, polymethylpentene, polyesters, rubbers or polyurethanes.

[0086] Examples of the soft cover sheet include laminated materials such as polypropylene sheets coated with aluminum foil.

[0087] The method for producing a covered medical device of the present invention comprises (C) a heating step of heating the container. In the heating step (C), the medical device is heated together with the container while in contact with the solution a containing the hydrophilic polymer A.

[0088] As the above-mentioned heating method, for example, heating method (hot air), high pressure steam sterilization, dry heat sterilization, flame sterilization, boiling sterilization, circulating steam sterilization, electromagnetic wave (gamma ray or microwave etc.) irradiation, ethylene oxide gas sterilization (EOG sterilization) or ultraviolet sterilization can be listed. From the aspect that sufficient lipid adhesion inhibition can be given to medical equipment and manufacturing cost is also low, high pressure steam sterilization is preferred, and autoclave sterilization using an autoclave as an apparatus is more preferred.

[0089] In order to impart sufficient lipid adhesion inhibition to the medical device without affecting the strength of the obtained covered medical device itself, the heating temperature is preferably 80 to 200° C. The heating temperature is more preferably 90° C. or higher, further preferably 105° C. or higher, further preferably 110° C. or higher, further preferably 115° C. or higher, and particularly preferably 121° C. or higher. In addition, the heating temperature is more preferably 180° C. or lower, further preferably 170° C. or lower, and particularly preferably 150° C. or lower.

[0090] In addition, for the same reason as the heating temperature, the heating time is preferably 1 to 600 minutes. The heating time is more preferably 2 minutes or more, further preferably 5 minutes or more, and particularly preferably 10 minutes or more. In addition, the heating time is more preferably 400 minutes or less, further preferably 300 minutes or less, and particularly preferably 100 minutes or less.

[0091] The manufacturing method of the covered medical device of the present invention is preferably: after the above-mentioned contact process and before the above-mentioned heating process, it is also provided with (B) a sealing process of sealing the above-mentioned container containing the above-mentioned medical device. In the case where the heating process is performed after the container containing the medical device is sealed, the obtained covered medical device can be sterilized while imparting lipid adhesion inhibition to the surface of the medical device, and the sterilized state can be maintained, which is industrially advantageous from the perspective of reducing the manufacturing process. That is, in the manufacturing method of the covered medical device of the present invention, in order to simplify the manufacturing process, it is preferably provided with a sealing process, and the medical device is sterilized by the above-mentioned heating process. Here, as a means for sealing the container, for example, a tube bottle or a blister container with a cover body can be listed as a container for storing medical devices to seal the container. In addition, in the case where the medical device is a contact lens, as a container for storing medical devices, as an example, a means for sealing the container by using a common lens box attached to contact lens care products can also be listed.

[0092] After the above-mentioned heating step, the obtained covered medical device may be further subjected to other treatments. Other treatments include, for example, the same heating treatment using a buffer solution that does not contain a hydrophilic polymer; irradiation with radiation such as ion beams, electron beams, positron beams, X-rays, gamma rays, or neutron beams; LbL treatment (Layer by Layer treatment; for example, the treatment described in International Publication No. 2013 / 024800) in which polymer materials with opposite charges are alternately applied layer by layer; or crosslinking treatment or chemical crosslinking treatment based on metal ions (for example, the treatment described in Japanese Patent Publication No. 2014-533381).

[0093] In addition, the surface of the medical device may be pretreated before the contact step and / or the heating step. Examples of the pretreatment include hydrolysis using an acid such as polyacrylic acid or an alkali such as sodium hydroxide.

[0094] In the manufacturing method of the covered medical device of the present invention, it is necessary to make the pH of the solution a after the above-mentioned heating process 6.1 to 8.0. By making the pH in this range, there is no need to use a neutral solution to clean the covered medical device obtained after the heating process, which is of great industrial significance from the perspective of reducing the manufacturing process. It should be noted that when a neutral solution is used for cleaning after the heating process, it is sometimes necessary to sterilize the obtained covered medical device again. The pH of the solution a after the heating process is preferably 6.5 or more, more preferably 6.6 or more, further preferably 6.7 or more, and particularly preferably 6.8 or more. In addition, the pH is preferably below 7.9, more preferably below 7.8, and further preferably below 7.6.

[0095] It should be noted that the pH of solution a before the heating step is also preferably 6.1 to 8.0. The pH of solution a is preferably 6.5 or more, more preferably 6.6 or more, further preferably 6.7 or more, and particularly preferably 6.8 or more. In addition, the pH is preferably 7.9 or less, more preferably 7.8 or less, and further preferably 7.6 or less. Here, the pH of solution a before the heating step refers to the pH value obtained by stirring solution a at room temperature (20 to 23°C) for 30 minutes using a rotor to make the solution uniform after preparation.

[0096] The pH of the solution a can be measured using a pH meter (for example, pH meter Eutech pH2700 (manufactured by Eutech Instruments)). The pH value is rounded to the second decimal place.

[0097] Preferably, there is no covalent bond between the covering layer, i.e., the hydrophilic polymer layer, and the medical device in the obtained covered medical device. Due to the absence of covalent bonds, whether the medical device is a water-containing material or a low-water-containing material, a simpler process can be used to manufacture the covered medical device. Here, the absence of covalent bonds means that there is no chemically reactive group or a group generated by its reaction between the hydrophilic polymer layer and the medical device. The absence of chemically reactive groups or groups generated by their reaction can be confirmed by elemental analysis or composition analysis means such as electron energy loss spectroscopy, energy dispersive X-ray spectroscopy, or time-of-flight secondary ion mass spectrometry. As chemically reactive groups, for example, azetidinium groups, epoxy groups, isocyanate groups, aziridine groups, or azlactone groups can be listed.

[0098] Regarding the thickness of the hydrophilic polymer layer, when a cross section perpendicular to the length direction of the covered medical device in a frozen state is observed using a transmission electron microscope, it is preferably 1 to 99 nm. By making the thickness of the hydrophilic polymer layer within this range, it is easy to express functions such as hydrophilicity and lubricity. The thickness of the hydrophilic polymer layer is more preferably 5 nm or more, and further preferably 10 nm or more. In addition, the thickness of the hydrophilic polymer layer is more preferably 95 nm or less, further preferably 90 nm or less, further preferably 85 nm or less, further preferably 50 nm or less, further preferably 40 nm or less, further preferably 30 nm or less, further preferably 20 nm or less, and particularly preferably 15 nm or less. It should be noted that in the case where the covered medical device is an ophthalmic lens, by making the thickness of the hydrophilic polymer layer less than 100 nm, the refraction of light used to focus on the retina will not be disturbed, and poor visual field is not likely to occur.

[0099] It should be noted that the covering layer in the obtained covered medical device may be present only on a part of the surface of the medical device, may be present only on the entire surface of any one side of the front or back, or may be present on the entire surface.

[0100] In the covered medical device of the present invention, in order to achieve a more secure covering, it is preferred that at least a portion of the hydrophilic polymer layer is mixed with the medical device. Here, the state in which the hydrophilic polymer layer is mixed with the medical device means that an element derived from the medical device is detected in the hydrophilic polymer layer. Whether an element derived from the medical device is detected in the hydrophilic polymer layer can be confirmed by observing the cross section of the covered medical device using elemental analysis or composition analysis methods such as scanning transmission electron microscopy, electron energy loss spectroscopy, energy dispersive X-ray spectroscopy, or time-of-flight secondary ion mass spectrometry.

[0101] If there is a mixed layer on the surface of the medical device, and the mixed layer is a layer in which at least a part of the hydrophilic polymer layer is mixed with the medical device, the hydrophilic polymer is firmly fixed to the surface of the medical device, so it is preferred. In the case of the presence of a mixed layer, it is preferred that a double-layer structure of the mixed layer and a single layer consisting only of a hydrophilic polymer can be observed in the hydrophilic polymer layer. Similar to the thickness of the above-mentioned hydrophilic polymer layer, the thickness of the mixed layer can be measured by observing a cross section perpendicular to the length direction of the covered medical device in a frozen state using a transmission electron microscope. In order to firmly fix the hydrophilic polymer on the surface of the medical device, the thickness of the mixed layer is preferably 3% or more, more preferably 5% or more, and further preferably 10% or more relative to the total thickness of the mixed layer and the single layer. In addition, in order to fully express the hydrophilicity of the hydrophilic polymer, the thickness of the mixed layer is preferably 98% or less, more preferably 95% or less, further preferably 90% or less, and particularly preferably 80% or less relative to the total thickness of the mixed layer and the single layer.

[0102] It is also preferred that in addition to the mixed layer on the surface of the medical device, a mixed part is observed. Here, the "mixed part" refers to a portion having no layer structure obtained by mixing a hydrophilic polymer with a medical device. That is, the so-called "mixed part is observed" means that a portion having no layer structure is observed in a portion other than the mixed layer on the surface of the medical device, and both elements derived from the hydrophilic polymer and elements derived from the medical device are detected in the portion. The thickness of the mixed part is preferably 3% or more, more preferably 5% or more, and further preferably 10% or more relative to the total thickness of the mixed layer and the mixed part. In addition, in order to fully express the hydrophilicity of the hydrophilic polymer, the thickness of the mixed part is preferably 98% or less, more preferably 95% or less, further preferably 90% or less, and particularly preferably 80% or less relative to the total thickness of the mixed layer and the mixed part.

[0103] When the covered medical device is an ophthalmic lens, etc., it is preferred that the liquid film covering the surface of the medical device be maintained for a long time from the viewpoint of preventing it from adhering to the wearer's cornea and less prone to dryness and maintaining a good wearing feeling for a long time.

[0104] Here, the retention time of the liquid film covering the surface of the medical device refers to the time during which the liquid film on the surface is maintained without rupture when the medical device is left to stand and immersed in a solution at room temperature (20-23°C), lifted from the solution, and held in the air in a manner such that the length direction of the device becomes the direction of gravity. In the case where the test piece is in the shape of a spherical crown such as a contact lens, it is maintained in a manner such that the diameter direction of the circle formed by the edge of the spherical crown becomes the direction of gravity. It should be noted that "liquid film rupture" means that a portion of the solution covering the surface of the medical device is repelled, and the surface of the medical device is no longer completely covered by the liquid film. It should be noted that if the liquid film retention time is too long, water is likely to evaporate from the surface of the medical device, and the hydrophilic effect becomes low. Therefore, the liquid film retention time is preferably 300 seconds or less, and more preferably 200 seconds or less.

[0105] When the covered medical device is an ophthalmic lens, etc., it is preferred that the liquid drop contact angle on the surface of the covered medical device is small from the viewpoint of not only preventing it from adhering to the cornea of ​​the wearer, but also not easily feeling dryness and being able to maintain a good wearing feeling for a long time. The method for measuring the liquid drop contact angle is described later. When the medical device is a material containing silicon atoms, the liquid drop contact angle is preferably 80° or less, preferably 70° or less, and more preferably 65° or less.

[0106] When the medical device is made of a material containing no silicon atoms, the droplet contact angle is preferably 70° or less, more preferably 60° or less, and even more preferably 55° or less.

[0107] In addition, the system with a small change in the droplet contact angle caused by scrubbing can be said to have formed a hydrophilic polymer layer with higher adsorption and better durability on the surface of the medical device. That is, the difference between the droplet contact angle (droplet contact angle X) after immersion in a new phosphate buffer for 24 hours and the droplet contact angle (droplet contact angle Y) after further scrubbing for 1 minute is focused on. The measurement method will be described later.

[0108] In the case where the covered medical device is, for example, a covered medical device to be inserted into a living body for use, its surface preferably has excellent slipperiness. The index representing slipperiness, i.e., the friction coefficient, is preferably 0.300 or less, more preferably 0.200 or less, further preferably 0.100 or less, and further preferably 0.080 or less. On the other hand, if the slipperiness is extremely high, sometimes the handling of the covered medical device becomes difficult, and therefore, the friction coefficient is preferably 0.001 or more, more preferably 0.002 or more. The method for measuring the friction coefficient will be described later.

[0109] In addition, the system with a small change in the friction coefficient caused by scrubbing can be said to have formed a hydrophilic polymer layer with higher adsorption and better durability on the surface of the medical device. That is, the difference between the friction coefficient after immersion in a new phosphate buffer for 24 hours (friction coefficient X) and the friction coefficient after further scrubbing for 1 minute (friction coefficient Y) is focused on. The measurement method will be described later.

[0110] In the case where the covered medical device is a soft medical device such as an ophthalmic lens, in order to improve the wearing feeling, the tensile elastic modulus is preferably 10.00MPa or less, more preferably 5.00MPa or less, further preferably 3.00MPa or less, further preferably 2.00MPa or less, further preferably 1.00MPa or less, and particularly preferably 0.60MPa or less. On the other hand, in order to facilitate handling, the tensile elastic modulus of the covered medical device is preferably 0.01MPa or more, more preferably 0.10MPa or more, further preferably 0.20MPa or more, and particularly preferably 0.25MPa or more. In addition, in the case of measuring the tensile elastic modulus of the medical device before the contact process and the heating process, and the covered medical device after the contact process and the heating process, in order to suppress the risk of deformation and poor use, the tensile elastic modulus change rate of the medical device before and after the contact process and the heating process, that is, before and after the covering is preferably ±15.00% or less, more preferably ±13.00% or less, and further preferably ±10.00% or less. The method for measuring the tensile elastic modulus is described below.

[0111] Regarding the covering of medical devices, in order to improve the usability and reduce the risk of bacterial growth, it is preferred that the amount of lipid attached is small. The method for measuring the amount of lipid attached will be described later.

[0112] When the covered medical device is an ophthalmic lens, in order to prevent poor visual field and deformation caused by refractive index distortion due to increased water content, the change in water content of the medical device before and after covering is preferably 10 percentage points or less, more preferably 8 percentage points or less, and even more preferably 6 percentage points or less. The method for measuring the water content will be described later.

[0113] When the covered medical device is an ophthalmic lens, in order to prevent corneal damage associated with deformation, the dimensional change rate of the medical device before and after covering is preferably ±5.00% or less, more preferably ±4.00% or less, and further preferably ±3.00% or less.

[0114] Example

[0115] Hereinafter, the present invention will be specifically described by way of Examples, etc., but the present invention is not limited thereto. First, the analysis method and the evaluation method in the Examples, etc. will be described.

[0116] <Hydrophilicity (Liquid Film Retention Time)>

[0117] After the heating process, the covered medical device (or medical device) that has been left to stand at room temperature (20-23°C) is lifted from the solution in the container and held in the air in such a way that its length direction becomes the direction of gravity. The time from the moment the device is held in the air to the moment a portion of the liquid film covering the surface of the device is broken is visually observed, and the average value of the value of N=3 is determined according to the following criteria. The maximum value measured is set to 120 seconds.

[0118] A: The liquid film on the surface is maintained for more than 20 seconds.

[0119] B: The surface liquid film breaks in 15 seconds or more and less than 20 seconds.

[0120] C: The surface liquid film breaks in 10 seconds or more and less than 15 seconds.

[0121] D: The surface liquid film breaks in 1 second or longer and less than 10 seconds.

[0122] E: The liquid film on the surface breaks in less than 1 second.

[0123] <Hydrophilicity after immersion in new phosphate buffer for 24 hours (Liquid film retention time after 24 hours)>

[0124] In order to remove the influence of the insufficiently adsorbed hydrophilic polymer on the surface of the medical device, the covered medical device or medical device after the heating process was left to stand in 4 mL of new phosphate buffer in a glass vial at room temperature (20-23°C) for 24 hours. Thereafter, the covered medical device or medical device taken out of the phosphate buffer in the glass vial was used as a sample (hereinafter referred to as "sample S") and the same evaluation as the above "hydrophilicity" was performed.

[0125] <Contact angle of droplet after immersion in new phosphate buffer for 24 hours (contact angle of droplet X)>

[0126] Prepare the above sample S separately, and use the contact angle measuring device (drop method) Drop master DM500 (manufactured by Kyowa Interface Science Co., Ltd.) to measure the drop contact angle. Specifically, after wiping off the moisture covering the surface of the medical device (or medical device), it is carried on a hemispherical polypropylene with a diameter of 14 mm, and the resulting substance is used as a sample. The sample is placed in a contact angle measuring device, and a phosphate buffer solution is added to the sample to measure the drop contact angle. The drop volume of the phosphate buffer solution added is set to 20 μL. The average value of the value of N=3 is taken as the drop contact angle.

[0127] <Contact angle of droplet after immersion in new phosphate buffer for 24 hours and further scrubbing for 1 minute (contact angle of droplet Y)>

[0128] The sample S was separately prepared, and the sample S was further held between fingers (thumb and index finger), and after rubbing for 1 minute, the same evaluation as the above-mentioned "liquid drop contact angle X" was performed.

[0129] <Water content of medical devices and covering medical devices>

[0130] The medical device provided before the manufacturing method of the present invention is immersed in a phosphate buffer solution and allowed to stand at room temperature (20-23°C) for more than 24 hours. Thereafter, the medical device is lifted out of the phosphate buffer solution, and the surface moisture is wiped off with a wipe cloth "KimWipes" (registered trademark) (manufactured by Nippon Paper Crecia Co., Ltd.), and the mass (Ww) of the medical device is measured. Thereafter, the medical device is dried at 40°C for 2 hours using a vacuum dryer, and the mass (Wd) of the medical device is measured. The water content of the medical device is calculated based on these masses using the following formula (1). When the obtained value is less than 1%, it is judged to be below the measurement limit and expressed as "less than 1%". The average value of the values ​​of N=3 is taken as the water content. The water content is calculated in the same manner for the covered medical device obtained after the heating process.

[0131] Water content of medical equipment (mass %) = 100 × (Ww - Wd) / Ww ... Formula (1).

[0132] <Change in moisture content of medical equipment before and after covering>

[0133] Based on the measurement results of the moisture content of the medical device and the covering medical device, the moisture content change amount is calculated using the following formula (2).

[0134] The change in moisture content of the medical device before and after covering (percentage points) = the moisture content of the covered medical device (mass %) - the moisture content of the medical device (mass %) ... Formula (2).

[0135] <Friction coefficient>

[0136] The friction coefficient of the surface of the covered medical device (or medical device) wetted with the phosphate buffer solution was measured at N=5 under the following conditions, and the average value of the values ​​of N=5 was taken as the friction coefficient.

[0137] Equipment: Friction Tester KES-SE (manufactured by Katotech Co., Ltd.)

[0138] Friction SENS: H

[0139] Measuring speed: 2×1mm / sec

[0140] Friction load: 44g.

[0141] <Friction coefficient after immersion in new phosphate buffer for 24 hours (friction coefficient X)>

[0142] The sample S was separately prepared and the same evaluation as the above-mentioned "friction coefficient" was performed.

[0143] <Friction coefficient after immersion in new phosphate buffer for 24 hours and further scrubbing for 1 minute (friction coefficient Y)>

[0144] The sample S was separately prepared, held between fingers (thumb and index finger), and scrubbed for 1 minute, followed by the same evaluation as in the above-mentioned "friction coefficient".

[0145] <Lipid Adhesion Amount>

[0146] Put 0.03g of methyl palmitate, 10g of pure water and the covered medical device (or medical device) into a 20cc threaded tube. Oscillate the threaded tube for 3 hours at 37°C and 165rpm. After oscillation, use 40°C tap water and household liquid detergent "Mama Lemon" (registered trademark) (manufactured by LION Co., Ltd.) to scrub the covered medical device (or medical device) in the threaded tube. Put the cleaned sample into a threaded tube filled with phosphate buffer and keep it in a refrigerator at 4°C for 24 hours. Thereafter, visually observe the covered medical device (or medical device). If there is a turbid part, it is judged to be attached with methyl palmitate, and observe the area of ​​the part with methyl palmitate attached relative to the entire surface of the sample.

[0147] <Tensile elastic modulus>

[0148] Use the specified punching die to cut a test piece with a width (minimum part) of 5 mm and a length of 14 mm from the covered medical device (or medical device). Use this test piece and TENSILON RTG-1210 (manufactured by A&D Co., Ltd.) to carry out the tensile test. The tensile speed is 100 mm / min, and the distance between the clamps (initial) is 5 mm. The measurement is performed on both the medical device before the contact process and the heating process, and the covered medical device after the contact process and the heating process. The measurement is performed with N=8, and the average value of the value of N=6 after removing the maximum and minimum values ​​is taken as the tensile elastic modulus.

[0149] <Change rate of tensile elastic modulus of medical devices before and after covering>

[0150] Based on the measurement results of the tensile elastic modulus, the change rate of the tensile elastic modulus of the medical device before and after covering was calculated using the following formula (3).

[0151] Change rate of tensile elastic modulus of the medical device before and after covering (%) = (tensile elastic modulus of the covered medical device after covering - tensile elastic modulus of the medical device before covering) / tensile elastic modulus of the medical device before covering × 100...Formula (3).

[0152] <Size>

[0153] The length of the covered medical device (or medical device) in the longitudinal direction (in the case of a circular contact lens, the diameter) is measured with N=3, and the average value of the N=3 values ​​is taken as the size.

[0154] <Dimensional change rate of medical devices before and after covering>

[0155] Based on the above-mentioned dimensional measurement results, the dimensional change rate before and after covering was calculated using the following formula (4).

[0156] Dimension change rate before and after covering (%) = (size of the covered medical device after covering - size of the medical device before covering) / size of the medical device before covering × 100 ... Formula (4).

[0157] <Weight Average Molecular Weight Measurement>

[0158] The weight average molecular weight (hereinafter referred to as "Mw") of the polymer was measured under the conditions shown below.

[0159] Equipment: Prominence GPC system (manufactured by Shimadzu Corporation)

[0160] Pump: LC-20AD

[0161] Automatic sample injector: SIL-20AHT

[0162] Column oven: CTO-20A

[0163] Detector: RID-10A

[0164] Column: GMPWXL (manufactured by Tosoh Corporation; inner diameter 7.8 mm × 30 cm, particle size 13 μm)

[0165] Solvent: Water / Methanol = 1 / 1 (with 0.1N lithium nitrate added)

[0166] Flow rate: 0.5mL / min

[0167] Measurement time: 30 minutes

[0168] Sample concentration: 0.1-0.3% by mass

[0169] Sample injection volume: 100 μL

[0170] Standard sample: polyethylene oxide standard sample (manufactured by Agilent; 0.1 kD to 1258 kD).

[0171] <ph>

[0172] The pH of the solution was measured using Eutech pH2700 (manufactured by Eutech Instruments) as a pH meter. The "pH after the heating step" of solution a was measured immediately after solution a was cooled to room temperature (20 to 23° C.) after the heating step.

[0173] <Thickness of Hydrophilic Polymer Layer>

[0174] The covered medical device (or medical device) is immersed in a phosphate buffer solution and left to stand for cleaning at room temperature (20-23°C) for more than 24 hours. Thereafter, an atomic resolution analytical electron microscope JEM-ARM200F (manufactured by JEOL) is used to observe the cross section perpendicular to the length direction of the frozen covered medical device (or medical device). Under the condition of an accelerating voltage of 200 kV, the measurement is performed while changing the position with N=3, and the average value of the value of N=3 is used as the thickness of the hydrophilic polymer layer. It should be noted that the measurement sample is prepared by the RuO4-stained frozen ultrathin section method.

[0175] <Analysis of Composition Elements of Hydrophilic Polymer>

[0176] In the hydrophilic polymer layer in the covering medical device, whether the hydrophilic polymer layer and the medical device are in a mixed state is determined by using time-of-flight secondary ion mass spectrometry (Time-of-Fright Secondary Ion Mass Spectrometry) to analyze the surface of the covering medical device (or medical device) in a dry state after being immersed in phosphate buffer and left to stand and wash at room temperature (20-23°C) for more than 24 hours.

[0177] Device: TOF.SIMS5 (manufactured by ION-TOF)

[0178] Observation conditions:

[0179] Primary ion: Bi 3++

[0180] Secondary ion polarity: positive

[0181] Etching ions: Ar-GCIB (gas cluster ion beam)

[0182] <Phosphate Buffer>

[0183] The composition of the phosphate buffer used in Examples and Comparative Examples is as follows.

[0184] KCl is 0.2g / L,

[0185] KH2PO4 is 0.2g / L,

[0186] NaCl is 8.0g / L,

[0187] Na2HPO4 is 1.19g / L,

[0188] EDTA2Na (ethylenediaminetetraacetic acid disodium dihydrogen) is 0.5g / L.

[0189] [Synthesis example 1]

[0190] In a 300 mL four-necked flask equipped with a stirrer, a thermometer, a condenser and a three-way stopcock, 114.08 g of distilled water, 21.62 g of side chain terminal hydrogen polyethylene glycol monoacrylate (manufactured by NOF Corporation, "BLEMMER" (registered trademark) AE-200), 4.5 polyethylene glycol chains (m in formula (I) = 4.5 (average value disclosed by the manufacturer), R 1 =Hydrogen, X=oxygen: 0.080 mol), 11.90 g of N,N-dimethylacrylamide (manufactured by KJ Chemical Co., Ltd., 0.120 mol), ultrasonic degassing and nitrogen replacement were performed 5 times. After the nitrogen replacement in the system was completed, the lower part of the flask was immersed in an oil bath set at 90°C while stirring. From the moment when the temperature inside the flask exceeded 70°C, 27.1 mg of polymerization initiator V-50 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., 0.0999 mmol) dissolved in 20.00 g of distilled water was added 6 times every 5 minutes. After adding all the polymerization initiators, the flask was kept warm at an internal temperature of 70-75°C for 4 hours to obtain a copolymer aqueous solution of side chain terminal hydrogen polyethylene glycol monoacrylate and polyethylene glycol chain number 4.5 / N,N-dimethylacrylamide (molar ratio in copolymerization 4 / 6, Mw: 250000).

[0191] [Synthesis example 2]

[0192] The addition amounts of the raw materials were set to 73.00 g of distilled water, 5.41 g of side chain terminal hydrogen polyethylene glycol monoacrylate ("BLEMMER" (registered trademark) AE-200, 0.020 mol), and 17.84 g (0.180 mol) of N,N-dimethylacrylamide. In addition, a polymer was prepared by the same method as in Synthesis Example 1 to obtain an aqueous solution of a copolymer of side chain terminal hydrogen polyethylene glycol monoacrylate and polyethylene glycol chain number 4.5 / N,N-dimethylacrylamide (molar ratio in copolymerization 1 / 9, Mw: 250000).

[0193] [Synthesis example 3]

[0194] In a 100 mL three-necked flask, 3.20 g of methoxytetraethylene glycol methacrylate (manufactured by NOF Corporation, "BLEMMER" (registered trademark) PME-200) was added. In the formula (II), a=0, k=2, b=4, R 1 = methyl, X = oxygen, Y = methyl: 11.6 mmol), 50.1 mg of 2,2'-azobis[2-(2-imidazoline-2-yl)propane] as a polymerization initiator (VA-061, 0.200 mmol, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), 28.23 g of distilled water (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), equipped with a digital thermometer, a Dimroth condenser equipped with a three-way stopcock, and a sealer with a stirring blade. Under ultrasonic irradiation, after suction to 10 mmHg, a cycle of nitrogen flash evaporation was repeated 5 times to remove dissolved oxygen in the mixed solution. Next, the lower part of the flask was immersed in an oil bath, and after reacting for 7 hours while stirring at 60°C, the reaction container was lifted out of the oil bath and air-cooled. 50 mL of methanol was added to the polymerization reaction solution and stirred. After reducing the viscosity, it was transferred to a 1L "Teflon" (registered trademark) beaker and heated and dried overnight in a vacuum dryer at 40°C. After drying, 5 mL of isopropyl alcohol (IPA) was added to the obtained viscous solid to dissolve it and allowed to stand in a refrigerator overnight. After cooling, the supernatant was removed by decantation and dried in a vacuum dryer at 30°C for 2 hours to obtain a white powder polymer. The Mw of the obtained methoxy polyethylene glycol methacrylate homopolymer (ethylene oxide repeating unit number 4) was 250,000.

[0195] [Reference Example 1]

[0196] 28.0 parts by mass of a polydimethylsiloxane represented by formula (M1) having methacryloyl groups at both ends (FM7726 manufactured by JNC Corporation, Mw: 30000), 7.0 parts by mass of an organosilicon monomer represented by formula (M2) (FM0721 manufactured by JNC Corporation, Mn: 5000), 57.9 parts by mass of trifluoroethyl acrylate (Viscoat (registered trademark) 3F manufactured by Osaka Organic Chemical Industry Co., Ltd.), 7.0 parts by mass of 2-ethylhexyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd.), and 0.1 parts by mass of dimethylaminoethyl acrylate (manufactured by Kojin Co., Ltd.), and 5000 ppm of a photoinitiator "Irgacure" (registered trademark) 819 (manufactured by Nagase Sangyo Co., Ltd.) based on the total mass of these monomers were prepared, as well as 5000 ppm of an ultraviolet absorber (RUVA-93 manufactured by Otsuka Chemical Co., Ltd.), and 100 ppm of a colorant (Arran Chemical Co., Ltd., RB246), and further prepare 10.0 parts by mass of tert-amyl alcohol relative to 100.0 parts by mass of the total mass of the above monomers, and all of them are mixed and stirred. The stirred mixture is filtered with a membrane filter (pore size: 0.45 μm) to remove insoluble components to obtain a monomer mixture.

[0197] The monomer mixture was injected into a contact lens mold made of a transparent resin (base curve side material: polypropylene, outer curve side material: polypropylene) and irradiated with light (wavelength 405nm (±5nm), illumination: 0-0.7mW / cm 2 , 30 minutes) and polymerize.

[0198] After polymerization, the obtained molded body, together with the mold from which the outer arc and the base arc were demolded, was immersed in a 100 mass % isopropyl alcohol aqueous solution at 60° C. for 1.5 hours, and the contact lens-shaped molded body was peeled off from the mold. The molded body thus obtained was immersed in a very excess amount of 100 mass % isopropyl alcohol aqueous solution maintained at 60° C. for 2 hours to extract impurities such as residual monomers. Then, it was dried at room temperature (23° C.) for 12 hours.

[0199] [Chemistry 7]

[0200]

[0201] [Chemistry 8]

[0202]

[0203] [Example 1]

[0204] As a "medical device", a commercially available silicone hydrogel lens "Acuvue Oasys" (registered trademark) (manufactured by Johnson & Johnson, senofilcon A) containing polyvinyl pyrrolidone and silicone as main components was used, as a "container", a glass vial was used, and as a "solution a", 3 mL of a solution containing 0.10% by mass of the hydrophilic polymer A obtained in the above-mentioned Synthesis Example 1, i.e., a side chain terminal hydrogen polyethylene glycol monoacrylate ("BLEMMER" (registered trademark) AE-200) / N,N-dimethylacrylamide copolymer (molar ratio in copolymerization 4 / 6, Mw: 250000) in a phosphate buffer solution was used. The above-mentioned medical device was immersed in the above-mentioned solution a ((A) contact step), the glass vial was sealed with a cap ((B) sealing step), and then heated at 121°C for 30 minutes using an autoclave ((C) heating step). The obtained covered medical device was evaluated by the above-mentioned method, and the results are shown in Tables 1 to 3.

[0205] [Example 2]

[0206] As solution a, 3 mL of a solution containing 0.30 mass % of the side chain terminal hydrogen polyethylene glycol monoacrylate ("BLEMMER" (registered trademark) AE-200) / N,N-dimethylacrylamide copolymer (molar ratio in copolymerization 1 / 9, Mw: 150000) obtained in the above Synthesis Example 2 in a phosphate buffer solution was used, and the same operation as in Example 1 was performed. The obtained covered medical device was evaluated by the above method, and the results are shown in Tables 1 to 3.

[0207] [Example 3]

[0208] As solution a, 0.60 mass % of polypropylene glycol monoacrylate (manufactured by NOF Corporation, "BLEMMER" (registered trademark) AP-400, a=0, k=3, b=6 (average values ​​disclosed by the manufacturer), R 1 The same operation as in Example 1 was performed except that 3 mL of a solution of a copolymer of 4 / 6 (molar ratio in copolymerization, Mw: 51000, manufactured by Osaka Organic Chemical Industry Co., Ltd.) and X=hydrogen, X=oxygen, Y=hydrogen was added. The obtained medical device was evaluated by the above method, and the results are shown in Tables 1 to 3.

[0209] [Example 4]

[0210] The same operation as in Example 1 was performed except that a commercially available hydrogel lens "Medalist 1 day plus" (registered trademark) containing 2-hydroxyethyl methacrylate as a main component (manufactured by Bausch & Lomb, hilafilcon B) was used as the medical device. The obtained covered medical device was evaluated by the above method, and the results are shown in Tables 1 to 3.

[0211] [Example 5]

[0212] The same operation as in Example 2 was performed except that a commercially available hydrogel lens "Medalist 1dayplus" (registered trademark) was used as the medical device. The obtained covered medical devices were evaluated by the above-mentioned method. The results are shown in Tables 1 to 3.

[0213] [Example 6]

[0214] As solution a, a phosphate buffer solution containing 0.60 mass % of polyethylene glycol polypropylene glycol monomethacrylate (manufactured by NOF Corporation, "BLEMMER" (registered trademark) 50PEP-300, wherein n=2, a=3.5, k=3, b=2.5, R 1 The same operation as in Example 1 was performed except that 3 mL of a solution of a copolymer of (4 / 6 molar ratio in copolymerization, Mw: 117,000, manufactured by Osaka Organic Chemical Industry Co., Ltd.) was added. The obtained covered medical device was evaluated by the above method, and the results are shown in Tables 1 to 3.

[0215] [Example 7]

[0216] The same operation as in Example 3 was performed except that a commercially available hydrogel lens "Medalist 1dayplus" (registered trademark) was used as the medical device. The obtained covered medical devices were evaluated by the above-mentioned method. The results are shown in Tables 1 to 3.

[0217] [Example 8]

[0218] The same operation as in Example 6 was performed except that a commercially available hydrogel lens "Medalist 1dayplus" (registered trademark) was used as the medical device. The obtained covered medical device was evaluated by the above-mentioned method. The results are shown in Tables 1 to 3.

[0219] [Example 9]

[0220] Instead of solution a, a solution containing 0.60 mass % of side chain terminal hydrogen polyethylene glycol monoacrylate (manufactured by NOF Corporation, "BLEMMER" (registered trademark) AE-400, m in formula (I) = 10 (average value disclosed by the manufacturer), R 1 = hydrogen, X = oxygen) / N,N-dimethylacrylamide copolymer (manufactured by Osaka Organic Chemical Industry Co., Ltd., molar ratio in copolymerization 4 / 6, Mw: 75000) was prepared in the same manner as in Example 1. The obtained covered medical device was evaluated by the above method, and the results are shown in Tables 1 to 3.

[0221] [Example 10]

[0222] The same operation as in Example 9 was performed except that a commercially available hydrogel lens "Medalist 1dayplus" (registered trademark) was used as the medical device. The obtained covered medical device was evaluated by the above-mentioned method. The results are shown in Tables 1 to 3.

[0223] [Example 11]

[0224] The same operation as in Example 1 was performed except that a commercially available hydrogel lens "1dayAcuvue" (registered trademark) (manufactured by Johnson & Johnson, etafilcon A) containing 2-hydroxyethyl methacrylate as a main component was used as the medical device. The obtained covered medical device was evaluated by the above method, and the results are shown in Tables 1 to 3.

[0225] [Example 12]

[0226] The same operation as in Example 9 was performed except that a commercially available hydrogel lens "1dayAcuvue" (registered trademark) was used as the medical device and a solution containing 0.60 mass % of the hydrophilic polymer A in a phosphate buffer solution was used as the solution A. The obtained covered medical device was evaluated by the above method, and the results are shown in Tables 1 to 3.

[0227] [Example 13]

[0228] As the medical device, the same operation as in Example 1 was performed except that a commercially available hydrogel lens "Proclea 1day" (registered trademark) (manufactured by Cooper Vision, omafilcon A) containing 2-hydroxyethyl methacrylate copolymerized with an MPC monomer (2-methacryloyloxyethyl phosphorylcholine) as a main component was used. The obtained covered medical device was evaluated by the above method, and the results are shown in Tables 1 to 3.

[0229] [Example 14]

[0230] The same operation as in Example 9 was performed except that a commercially available hydrogel lens "Proclea 1day" (registered trademark) was used as the medical device and a solution containing 0.60 mass % of the hydrophilic polymer A in a phosphate buffer solution was used as the solution A. The obtained covered medical device was evaluated by the above method, and the results are shown in Tables 1 to 3.

[0231] [Example 15]

[0232] The same operation as in Example 1 was performed except that a commercially available hydrogel colored lens "1day Acuvue Define Moist" (registered trademark) (manufactured by Johnson & Johnson, etafilcon A) containing 2-hydroxyethyl methacrylate as a main component was used as the medical device. The obtained covered medical device was evaluated by the above method. The results are shown in Tables 1 to 3.

[0233] [Example 16]

[0234] The same operation as in Example 9 was performed except that a commercially available hydrogel color lens "1day Acuvue Define Moist" (registered trademark) was used as the medical device and a solution containing 0.70 mass % of the hydrophilic polymer A in a phosphate buffer solution was used as the solution A. The obtained covered medical device was evaluated by the above method, and the results are shown in Tables 1 to 3.

[0235] [Example 17]

[0236] The same operation as in Example 1 was performed except that a commercially available silicone hydrogel lens "1day Acuvue Trueye" (registered trademark) (manufactured by Johnson & Johnson, narafilcon A) containing polyvinyl pyrrolidone and silicone as main components was used as the medical device. The obtained covered medical device was evaluated by the above method, and the results are shown in Tables 1 to 3.

[0237] [Example 18]

[0238] The same operation as in Example 9 was performed except that a commercially available silicone hydrogel lens "1day Acuvue Trueye" (registered trademark) was used as the medical device and a solution containing 0.80 mass % of the hydrophilic polymer A in a phosphate buffer solution was used as the solution A. The obtained covered medical device was evaluated by the above method, and the results are shown in Tables 1 to 3.

[0239] [Example 19]

[0240] The same operation as in Example 1 was performed except that a commercially available silicone hydrogel lens "AIR OPTIX AQUA" (registered trademark) (manufactured by Japan ALCON Co., Ltd., lotrafilcon A) containing silicone as the main component and having a plasma-treated lens surface was used as the medical device. The obtained covered medical device was evaluated by the above method, and the results are shown in Tables 1 to 3.

[0241] [Example 20]

[0242] The same operation as in Example 9 was performed except that a commercially available silicone hydrogel lens "AIR OPTIX AQUA" (registered trademark) was used as the medical device and a solution containing 0.90 mass % of the hydrophilic polymer A in a phosphate buffer solution was used as the solution A. The obtained covered medical device was evaluated by the above method, and the results are shown in Tables 1 to 3.

[0243] [Example 21]

[0244] The same operation as in Example 1 was performed except that the molded article obtained in Reference Example 1 was used as the medical device and a solution containing 0.60 mass % of the hydrophilic polymer A in a phosphate buffer solution was used as the solution A. The results of evaluation of the obtained covered medical devices by the above method are shown in Tables 1 to 3.

[0245] [Example 22]

[0246] The same operation as in Example 9 was performed except that the molded article obtained in Reference Example 1 was used as the medical device and a solution containing 5.00 mass % of the hydrophilic polymer A in a phosphate buffer solution was used as the solution A. The obtained covered medical device was evaluated by the above method, and the results are shown in Tables 1 to 3.

[0247] [Table 1]

[0248]

[0249] [Table 2]

[0250]

[0251] [Table 3]

[0252]

Table 3

[0253]

[0254] [Comparative Example 1]

[0255] The same operation as in Example 1 was performed except that a solution containing 0.20 mass % of acrylic acid / vinyl pyrrolidone / N,N-dimethylacrylamide copolymer (molar ratio in copolymerization: 1 / 1 / 2, Mw: 550000, manufactured by Osaka Organic Chemical Industry Co., Ltd.) in phosphate buffer was used instead of solution a. The obtained covered medical device (hydrophilic polymer layer was not confirmed) was evaluated by the above method, and the results are shown in Tables 4 to 6.

[0256] [Comparative Example 2]

[0257] The same operation as in Example 1 was performed except that a solution containing 0.10 mass % of acrylic acid / vinyl pyrrolidone / N,N-dimethylacrylamide copolymer (molar ratio in copolymerization: 1 / 1 / 2, Mw: 330000, manufactured by Osaka Organic Chemical Industry Co., Ltd.) in phosphate buffer was used instead of solution a. The obtained covered medical device (hydrophilic polymer layer was not confirmed) was evaluated by the above method, and the results are shown in Tables 4 to 6.

[0258] [Comparative Example 3]

[0259] The same operation as in Example 1 was performed except that a solution containing 0.10 mass % of acrylic acid / N,N-dimethylacrylamide copolymer (manufactured by Osaka Organic Chemical Industry Co., Ltd., molar ratio in copolymerization 1 / 9, Mw: 300000) in phosphate buffer was used instead of solution a. The obtained covered medical device (hydrophilic polymer layer was not confirmed) was evaluated by the above method, and the results are shown in Tables 4 to 6.

[0260] [Comparative Example 4]

[0261] As a medical device, a commercially available hydrogel lens "Medalist 1dayplus" (registered trademark) (manufactured by Bausch & Lomb, hilafilcon B) was used, and a solution containing 0.30 mass % of polyethylene glycol (manufactured by Wako Pure Chemical Industries, Ltd., Mw: 500000) in a phosphate buffer was used instead of solution a. The same operation as in Example 1 was performed. The obtained covered medical device (hydrophilic polymer layer was not confirmed) was evaluated by the above method, and the results are shown in Tables 4 to 6.

[0262] [Comparative Example 5]

[0263] The same operation as in Example 1 was performed except that a solution containing 0.10 mass % of an acrylic acid / vinyl pyrrolidone copolymer (manufactured by Osaka Organic Chemical Industry Co., Ltd., molar ratio in copolymerization 1 / 4, Mw: 590000) in a phosphate buffer was used instead of solution a. The obtained covered medical device (hydrophilic polymer layer was not confirmed) was evaluated by the above method, and the results are shown in Tables 4 to 6.

[0264] [Comparative Example 6]

[0265] The same operation as in Example 1 was performed except that a solution containing 0.10 mass % of an acrylic acid / vinyl pyrrolidone copolymer (manufactured by Osaka Organic Chemical Industry Co., Ltd., molar ratio in copolymerization 1 / 9, Mw: 390000) in a phosphate buffer was used instead of solution a. The obtained covered medical device (hydrophilic polymer layer was not confirmed) was evaluated by the above method, and the results are shown in Tables 4 to 6.

[0266] [Comparative Example 7]

[0267] The same operation as in Example 1 was performed except that a solution containing 0.20 mass % of acrylic acid / 2-hydroxyethyl methacrylate / N,N-dimethylacrylamide copolymer (manufactured by Osaka Organic Chemical Industry Co., Ltd., molar ratio in copolymerization 1 / 1 / 2, Mw: 430000) in phosphate buffer was used instead of solution a. The obtained covered medical device (hydrophilic polymer layer was not confirmed) was evaluated by the above method, and the results are shown in Tables 4 to 6.

[0268] [Comparative Example 8]

[0269] The same operation as in Example 1 was performed except that a solution containing 0.20 mass % of acrylic acid / 2-hydroxyethyl methacrylate / N,N-dimethylacrylamide copolymer (manufactured by Osaka Organic Chemical Industry Co., Ltd., molar ratio in copolymerization 1 / 1 / 8, Mw: 480000) in phosphate buffer was used instead of solution a. The obtained covered medical device (hydrophilic polymer layer was not confirmed) was evaluated by the above method, and the results are shown in Tables 4 to 6.

[0270] [Comparative Example 9]

[0271] The same operation as in Example 1 was performed except that a solution containing 0.30 mass % of polyvinyl pyrrolidone (manufactured by Osaka Organic Chemical Industry Co., Ltd., Mw: 500000) in a phosphate buffer was used instead of solution a. The obtained covered medical device (hydrophilic polymer layer was not confirmed) was evaluated by the above method, and the results are shown in Tables 4 to 6.

[0272] [Comparative Example 10]

[0273] The same operation as in Example 1 was performed except that a solution containing 0.30 mass % of poly-N,N-dimethylacrylamide (manufactured by Wako Pure Chemical Industries, Ltd., Mw: 700000) in a phosphate buffer was used instead of solution a. The obtained covered medical device (hydrophilic polymer layer was not confirmed) was evaluated by the above method, and the results are shown in Tables 4 to 6.

[0274] [Comparative Example 11]

[0275] The same operation as in Example 1 was performed except that a phosphate buffer solution was used instead of Solution a. The obtained medical device (polymer layer was not confirmed) was evaluated by the above-mentioned method. The results are shown in Tables 4 to 6.

[0276] [Comparative Example 12]

[0277] The same operation as in Comparative Example 11 was performed except that a commercially available hydrogel lens "Medalist 1dayplus" (registered trademark) was used as the medical device. The obtained medical device (polymer layer was not confirmed) was evaluated by the above method. The results are shown in Tables 4 to 6.

[0278] [Comparative Example 13]

[0279] The same operation as in Comparative Example 10 was performed except that a commercially available hydrogel lens "Medalist 1dayplus" (registered trademark) was used as the medical device. The obtained medical device (polymer layer was not confirmed) was evaluated by the above method. The results are shown in Tables 4 to 6.

[0280] [Comparative Example 14]

[0281] The same operation as in Comparative Example 13 was performed except that a solution containing 0.20 mass % of the methoxypolyethylene glycol methacrylate homopolymer (polyethylene glycol chain number 4, Mw: 250000) obtained in the above Synthesis Example 3 was used in phosphate buffer instead of Solution a. The obtained covered medical device (hydrophilic polymer layer was not confirmed) was evaluated by the above method, and the results are shown in Tables 4 to 6.

[0282] [Comparative Example 15]

[0283] The same operation as in Comparative Example 13 was performed except that a solution containing 0.20 mass % of the methoxypolyethylene glycol methacrylate homopolymer obtained in Synthesis Example 3 in a phosphate buffer was used instead of Solution a. The obtained covered medical device (hydrophilic polymer layer not confirmed) was evaluated by the above method, and the results are shown in Tables 4 to 6.

[0284] [Comparative Example 16]

[0285] The same operation as in Example 1 was performed except that a solution containing 0.20 mass % of the methoxypolyethylene glycol methacrylate homopolymer obtained in Synthesis Example 3 in phosphate buffer was used instead of Solution a. The obtained covered medical device (hydrophilic polymer layer not confirmed) was evaluated by the above method, and the results are shown in Tables 4 to 6.

[0286] [Comparative Example 17]

[0287] The same operation as in Comparative Example 11 was performed except that a commercially available hydrogel lens "1dayAcuvue" (registered trademark) was used as the medical device. The obtained medical device (polymer layer was not confirmed) was evaluated by the above method. The results are shown in Tables 4 to 6.

[0288] [Comparative Example 18]

[0289] The same operation as in Comparative Example 11 was performed except that a commercially available hydrogel lens "Proclea 1day" (registered trademark) was used as the medical device. The obtained medical device (polymer layer was not confirmed) was evaluated by the above method. The results are shown in Tables 4 to 6.

[0290] [Comparative Example 19]

[0291] The same operation as in Comparative Example 11 was performed except that a commercially available hydrogel color lens "1day Acuvue Define Moist" (registered trademark) was used as the medical device. The obtained medical device (polymer layer not confirmed) was evaluated by the above method. The results are shown in Tables 4 to 6.

[0292] [Comparative Example 20]

[0293] The same operation as in Comparative Example 11 was performed except that a commercially available silicone hydrogel lens "1day Acuvue Trueye" (registered trademark) was used as the medical device. The obtained medical device (polymer layer not confirmed) was evaluated by the above method. The results are shown in Tables 4 to 6.

[0294] [Comparative Example 21]

[0295] The same operation as in Comparative Example 11 was performed except that a commercially available silicone hydrogel lens "AIR OPTIX AQUA" (registered trademark) was used as the medical device. The obtained medical device (polymer layer was not confirmed) was evaluated by the above method. The results are shown in Tables 4 to 6.

[0296] [Comparative Example 22]

[0297] The same operation as in Comparative Example 11 was performed except that the molded article obtained in Reference Example 1 was used as the medical device. The obtained medical device (polymer layer was not confirmed) was evaluated by the above-mentioned method. The results are shown in Tables 4 to 6.

[0298] [Table 4]

[0299]

[0300] [Table 5]

[0301]

[0302] [Table 6]

[0303]

Table 6

[0304]

[0305] From the comparison between the results of the examples and the comparative examples, it is understood that the present invention can impart not only sufficient hydrophilicity and lubricity to medical devices, but also excellent lipid adhesion inhibition properties.

[0306] In addition, when focusing on the changes in the droplet contact angle and the friction coefficient caused by scrubbing, that is, the difference between the droplet contact angle X and the droplet contact angle Y, and the difference between the friction coefficient X and the friction coefficient Y, the system with a small amount of change can be said to form a hydrophilic polymer layer with higher adsorption force and better durability on the surface of the medical device. The results of Examples 4 and 5, and 10 to 16 are equivalent to this.< / ph>

Claims

1. A covered medical device comprising a medical device and a hydrophilic polymer layer covering the surface of the medical device, wherein: The hydrophilic polymer layer comprises a hydrophilic polymer A, The hydrophilic polymer A comprises a compound a1 represented by the following general formula (I) or the following general formula (II) and a compound a2 having an amide group as monomer units. The copolymerization ratio of the compound a1 to the compound a2 is 1 / 99 to 90 / 10 in terms of mass ratio, [Chemistry 1] In the general formula (I), R 1 represents a hydrogen atom or a methyl group, and X represents an oxygen atom or NR 2 , R 2 represents a hydrogen atom or an alkyl group, and m represents an integer of 1 to 30; [Chemistry 2] In the general formula (II), R 1 represents a hydrogen atom or a methyl group, and X represents an oxygen atom or NR 2 , R 2 represents a hydrogen atom or an alkyl group, n represents 2 or 4, k represents 3 or 4, a represents an integer of 0 to 30, b represents an integer of 1 to 30, and Y represents a hydrogen atom, methyl, ethyl, propyl, isopropyl or butyl. 2 . The covered medical device according to claim 1 , comprising a mixed layer of the hydrophilic polymer layer and the medical device.

3. The covered medical device according to claim 1 or 2, wherein: The medical device comprises a material selected from the group consisting of a hydrogel, a silicone hydrogel, a low water content soft material, and a low water content hard material.

4. The covered medical device according to claim 3, wherein: The hydrogel is selected from the group consisting of tefilcon, tetrafilcon, helfilcon, mafilcon, polymacon, hioxifilcon, alfafilcon, omafilcon, nelfilcon, nesofilcon, hilafilcon, acofilcon, deltafilcon, etafilcon, focofilcon, ocufilcon, phemfilcon, methafilcon and vilfilcon.

5. The covered medical device according to claim 3, wherein: The silicone hydrogel is selected from lotrafilcon, galyfilcon, narafilcon, senofilcon, comfilcon, enfilcon, balafilcon, efrofilcon, fanfilcon, somofilcon, samfilcon, olifilcon, asmofilcon, formofilcon, stenfilcon, abafilcon, mangofilcon, riofilcon, sifilcon, larafilcon and delefilcon.

6. The covered medical device according to claim 3, wherein: The low-water-content soft material or the low-water-content hard material is selected from polysulfone, polystyrene, polymethyl methacrylate, polyurethane and polyamide.

7. The covered medical device according to any one of claims 1 to 6, wherein: The medical device is selected from eye lenses, skin covering materials, wound covering materials, skin protective materials, skin drug carriers, infusion tubes, gas delivery tubes, drainage tubes, blood circuits, covering tubes, catheters, stents, sheaths, biosensor chips, artificial hearts and lungs, and endoscope covering materials.

8. The method for manufacturing a covered medical device according to any one of claims 1 to 7, comprising: (A) a contacting step of placing a medical device in a container and bringing the medical device into contact with a solution a containing a hydrophilic polymer A; and (C) a heating step of heating the container, The hydrophilic polymer A comprises a compound a1 represented by the following general formula (I) or the following general formula (II) and a compound a2 having an amide group as monomer units, The copolymerization ratio of the compound a1 to the compound a2 is 1 / 99 to 90 / 10 in terms of mass ratio, [Chemistry 3] In the general formula (I), R 1 represents a hydrogen atom or a methyl group, and X represents an oxygen atom or NR 2 , R 2 represents a hydrogen atom or an alkyl group, and m represents an integer of 1 to 30; [Chemistry 4] In the general formula (II), R 1 represents a hydrogen atom or a methyl group, and X represents an oxygen atom or NR 2 , R 2 represents a hydrogen atom or an alkyl group, n represents 2 or 4, k represents 3 or 4, a represents an integer of 0 to 30, b represents an integer of 1 to 30, and Y represents a hydrogen atom, methyl, ethyl, propyl, isopropyl or butyl; The pH of the solution a after the heating step is 6.1 to 8.

0. 9 . The method for manufacturing a covered medical device according to claim 8 , further comprising (B) a sealing step of sealing the container storing the medical device.

10. The method for manufacturing a covered medical device according to claim 8 or 9, wherein: The medical device is sterilized by the heating process.

Citation Information

Patent Citations

  • Arukaridenchi

    JP1976054231A

  • Cross-linked hydrophilic coated silicone hydrogel lens

    JP2014533381A

  • Medical treatment device, composition for coating solution, and method for manufacturing medical treatment device

    WO2013024799A1

  • Low-moisture-content soft device and method for producing same

    WO2013024800A1

  • Lens solution, contact lens, and production method therefor

    WO2015119256A1